Polychaetes from the coast of northern Cyprus (eastern Mediterranean Sea), with two new records for the Mediterranean Sea - Çinar, M. E. (Cahiers de Biologie Marine, 2005)
Faunistic analysis of polychaetes collected during two cruises performed along the northern Cyprus in May 1997 and June 1998 yielded a total of 384 species belonging to 45 families. Among them, two species, namely Oenone cf. fulgida (Savigny, 1818) and Notomastus mossambicus (Thomassin, 1970), were new to the Mediterranean fauna, 19 species new to the eastern Mediterranean fauna, 90 species new to the Levant fauna and 209 species new to the Cypriot fauna, bringing the total number of taxa known from Cyprus to 456 species. A total of 11 polychaete species, which were previously regarded as Lessepsian species, were encountered, of which 7 are being newly reported for the first time along the coast of Cyprus. Two species new to the Mediterranean Sea, which could also be Lessepsian species as they have Indo-Pacific distributions, were redescribed and discussed.
World Polychaeta Database (WPolyDb). Open access article